TRAJECTORY ERROR MINIMISATION METHOD DUE TO TRANSIENT REGIME VARIATION OF INDUSTRIAL ROBOTS KINEMATIC LINKS - ANDREI LUNCANU; GHEORGHE STAN (Journal of Engineering Studies and Research)
In the current industry, industrial robots are gaining more and more ground to classical positioning methods, especially due to the ratio of workspace / volume of the industrial robot. For this reason, methods of minimization of trajectory errors are necessary. Among the multitudes of factors that affect the trajectory precision is the difference between the programmed transient regime and the measured transient regime of the kinematic link used in the structure of the industrial robots. In this paper is presented the method of measurement the transient regimes of the end-effector and a method of compensation of the trajectory error.